Antioxidant and Renoprotective Effects of Mushroom Extract: Implication in Prevention of Nephrolithiasis - Schulman, Ariel (J Clin Med Res, 2016)
BACKGROUND: The pathogenesis of nephrolithiasis (kidney stone) remains elusive, while several therapeutic options are available but not effective as we expected. Accumulating data yet suggest that oxidative stress (generation of oxygen free radicals) may play a primary role in its occurrence. Particularly, calcium oxalate (CaOx) is a key element in the most common form (> 75%) of kidney stones, and its crystal form known as CaOx monohydrate (COM) has been shown to exert oxidative stress, facilitating CaOx stone formation. Hence, diminishing oxidative stress with certain antioxidants could be a potential strategic approach. We are interested in a bioactive extract of Poria mushroom, PE, which has been shown to have antioxidant and renoprotective activities. Accordingly, we investigated if PE might have antioxidant activity that would have implication in prevention of kidney stone formation. METHODS: Renal epithelial LLC-PK(1) cells were employed and exposed to COM or hydrogen peroxide (H(2)O(2)) as a positive control capable of exerting oxidative stress. Possible antioxidant and protective effects of PE against oxidative stress (exerted by COM or H(2)O(2)) were assessed by cell viability test and lipid peroxidation (LPO) assay. To explore its protective mechanism, two glycolytic parameters, hexokinase (HK) activity and ATP synthesis, were examined and cell cycle analysis was also performed. RESULTS: Both H(2)O(2) and COM led to a significant (P < 0.05) reduction in cell viability, accompanied by severe oxidative stress assessed by LPO assay. Such oxidative stress also caused the significant decline in HK activity and cellular ATP level, indicating the inhibition of glycolysis. Cell cycle analysis further indicated that oxidative stress interfered with cell cycle, inducing a G(1) cell cycle arrest that presumably results in the cessation of cell proliferation. However, PE was capable of significantly preventing or diminishing all these cellular effects mediated through oxidative stress (exerted by H(2)O(2) and COM). CONCLUSIONS: The present study shows that the mushroom extract PE appears to have antioxidant and renoprotective effects against oxidative stress exerted by COM in renal cells. Therefore, PE with antioxidant activity is considered a promising natural agent that may have clinical implications in prevention of nephrolithiasis primarily induced by oxidative stress.